Transformasi SDM Sekolah Melalui Kaizen Menuju Pendidikan yang Kompetetif di Era Ekonomi Global - Rizal, Mohammad SYifaur (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study discusses the transformation of school human resources (HR) through the application of Kaizen principles as a strategy to realize competitive education in the era of the global economy. This study employs a qualitative method with a descriptive approach, focusing on a case study at SMA Tunas Luhur. Data were obtained through in-depth interviews, observations, and documentation studies of the principal, curriculum vice principal, and infrastructure vice principal. The results of the study indicate that the implementation of the five Kaizen principles—Seiri, Seiton, Seiso, Seiketsu, and Shitsuke—has succeeded in improving the quality of HR through needs-based training, spatial arrangement and teaching materials, cleanliness habits, learning standardization, and instilling sustainable work discipline. The synergy between school leaders and the management team is the main factor in the success of this transformation. These findings reinforce that Kaizen is not only a strategic managerial approach, but also a cultural approach that can form an adaptive, efficient, and high-quality work culture in educational institutions.